Reflection of Marxist Ideologies through the Film ‘Asuran (2019)’ - K, Akash (Journal of Advanced Research in Journalism & Mass Communication, 2023)
This research study focuses on the analysis of reflection of Marxist ideology through the Asuran film (2019), which is directed by Vetrimaaran. The contemporary marxist film is observed contextually through the historic literary work of Kral Marx. The attributes derived from the literary works of Marxism by Karl Marx and Friedrich Engles from their books- The Communist Manifesto (1848), Das Kapital (1867) and The German ideology (1932) have become the core marxist principles for this study. Among them, the core concepts of Marxism include - class conflict, base and superstructure, false consciousness, class consciousness alienation, materialism, and Capitalistic society are chosen as variables. In borrowing those marxist ideas the researcher has observed and analysed it through thematic, characteristic and symbolic representation in the Asuran Film. This research gave findings of how to understand film through marxist approach. The researcher did understand the relevance of marxism in storytelling, how marxist elements can be used in building story and what all should be present to consider a movie is oriented to marxist ideology. How to cite this article: Akash K. Reflection of Marxist Ideologies through the Film ‘Asuran (2019)’. J Adv Res Jrnl Mass Comm 2023; 10(1): 8-12. DOI: https://doi.org/10.24321/2395.3810.202302